2013
DOI: 10.1179/1476830513y.0000000076
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal molybdenum exposure and infant neurodevelopment in Mexican children

Abstract: As this is the first study that suggests a potential negative association between prenatal Mo exposure and infant neurodevelopment, these results require further confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Mo is considered an essential trace element. Due to the small sample size of this study, the scarce evidence about its potential toxicity in humans, 13,15,16,35,36 further research with a larger sample size and a detail evaluation of other potential dietary and environmental sources of Mo is warranted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mo is considered an essential trace element. Due to the small sample size of this study, the scarce evidence about its potential toxicity in humans, 13,15,16,35,36 further research with a larger sample size and a detail evaluation of other potential dietary and environmental sources of Mo is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…However, in children from these women we observed a negative association between prenatal Mo exposure and infant psychomotor neurodevelopment. 16 Similarly, two studies have observed a possible association between Mo exposure with spermatic damage, 35 reproductive hormone alterations 36 and liver disorders 15 at BEs levels associated with toxicity in whole blood (0.45-22mg/L) or lower than those urinary BEs proposal levels for Mo.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Molybdenum is present in sulfite oxidase -an enzyme located in mitochondria that is responsible for amino acid and lipid metabolism (97). Little is known about the role of molybdenum in humans but it has been proposed that molybdenum has an association with neurodevelopment (98).…”
Section: Molybdenum (Mo)mentioning
confidence: 99%